Pelatihan Budidaya Ikan Lele Sistem Aquaponik dan Manajemen Usaha Bagi Kelompok Masyarakat di Kelurahan Amban, Kabupaten Manokwari - Pattiasina, Thomas Frans; Aman, Wilson Palelingan; Wambrauw, Ludia T.; Ruimassa, Reymas M. R. (Abdimas Indonesian Journal, 2024)
Catfish is one of the leading commodities of inland fisheries in Manokwari Regency. However, community cultivation businesses are still conventional, with minimal business capital, low human resource capacity and technological capabilities, and business management that has not run well. The purpose of this activity is to provide training and assistance on the application of appropriate technology in catfish farming as well as good and correct business management to the fish farming community in Amban Village, especially KUT PETRA. This community service will be carried out in 3 stages, namely: the preparation stage, the implementation stage and the evaluation stage. The preparation stage includes the preparation of training materials, the preparation of activity administration and the socialization of activity plans to partners. The implementation stage includes training activities, work practices and assistance for catfish farming aquaponic systems and business financial management. The evaluation stage is carried out based on the results of monitoring. The results that have been achieved from this activity are the implementation of catfish cultivation technology training activities with aquaponic systems and business financial management, and have been continued with practical work activities for making aquaponic system aquaculture media construction and business financial bookkeeping. The activity has been carried out well and partners have benefited in the form of knowledge and skills in catfish farming technology, aquaponic systems and the ability to manage business finances. The next activity that will still be carried out is business assistance and fulfillment of the outputs of this community service activity.